The Influence of Sports Mega-Events on Local Business Growth: A Study of PON 2024 Aquatic Venue - Pijai Prana Sitepu; Rama Wati; Agnes Monica Hutahaean; Revaldi Sembiring; Ricky Ariya Sitepu (Global Insights in Management and Economic Research, 2025)
Introduction: Sports mega-events have emerged as significant catalysts for regional economic development, yet their impact on local business ecosystems remains inadequately understood, particularly in developing economies. The Pekan Olahraga Nasional (PON) 2024, hosted in Papua, Indonesia, presents a unique opportunity to examine these dynamics within an emerging market context. Purpose of the study: This research investigates the influence of PON 2024's aquatic venue on local business growth, examining both immediate and sustained economic impacts on small and medium enterprises (SMEs) in the host region. Materials and methods: A mixed-methods approach was employed, involving 387 local businesses across hospitality, retail, transportation, and service sectors. Data collection occurred through structured surveys, financial performance analysis, and semi-structured interviews conducted pre-event (6 months prior), during the event, and post-event (6 months after). Quantitative analyses were conducted using SPSS v27, employing descriptive statistics, paired t-tests, and multiple regression analysis. Results: Local businesses experienced a mean revenue increase of 34.7% (SD = 12.3) during the event period compared to baseline measurements. The hospitality sector demonstrated the highest growth (47.2%), followed by retail (31.8%) and transportation services (28.4%). Post-event analysis revealed sustained growth of 18.3% above baseline levels six months after conclusion. Employment increased by 23.1% during the event, with 67.4% of new positions retained post-event. Conclusions: PON 2024's aquatic venue generated substantial positive impacts on local business growth, with effects extending beyond the immediate event period. The findings suggest that well-planned sports mega-events can serve as effective tools for regional economic development, particularly when integrated with comprehensive local business development strategies.